International monetary policy coordination and financial market integration - Alan Sutherland (European Central Bank (ECB), 2002)
The welfare gains from international co-ordination of monetary policy are analysed in a two-country model with sticky prices. The gains from co-ordination are compared under two alternative structures for financial markets: financial autarky and risk sharing. The welfare gains from co-ordination are found to be largest when there is risk sharing and the elasticity of substitution between home and foreign goods is greater than unity. When there is no risk sharing the gains to co-ordination are almost zero. It is also shown that the welfare gain from risk sharing can be negative when monetary policy is uncoordinated.
Keywords: E52; E58; F42; 330